Endovascular medicine certification 2005–2014: Report from the American Board of Vascular Medicine. (June 2015) - Slovut, David Paul; Saiar, Amin; Gray, Bruce H; ,
This report describes the methods used to develop and maintain the endovascular medicine certification examination, which has been offered by the American Board of Vascular Medicine (ABVM) to practicing physicians since 2005. The report covers the methods and findings used to develop examination specifications which ensure the content and construct validity of the examination assessment such that the examination is reflective of the job tasks associated with the endovascular medicine specialty, as well as being a meaningful indicator of whether a candidate possesses the knowledge and skills necessary for competent practice. Further, this report covers the procedures used to develop, maintain, and administer the examination, including a summary of the content review process and the use of statistical information. Based on psychometric evaluation of the examination's performance, the ABVM's endovascular medicine examination appears to be a valid assessment of professional competency in the specialty area; a finding that supports the inference that candidates who pass the examination are qualified to practice in a manner that protects patients.